Analysis of Melinjo Seed Extract as Corrosion Bioinhibitor for Ferrous Metals - Mubarok, Zakky; Fikroh, Retno Aliyatul (Universitas Nusa Bangsa, 2024)
The corrosion of ferrous metals is a serious issue that can reduce material durability and lead to significant economic losses. Melinjo seed extract was selected for investigation due to its potential as a corrosion inhibitor, attributed to the presence of tannin compounds capable of forming complexes that coat metal surfaces. This research aims to explore the use of melinjo seed extract as a bioinhibitor for iron, providing an effective and environmentally friendly solution. The extraction of melinjo seeds was performed using the maceration method. The melinjo seed extract was mixed with 70% ethanol to obtain an inhibitor solution. The study evaluated the corrosion rate and inhibition efficiency of iron immersed in melinjo seed extract solution at varying concentration. The results showed that melinjo seed extract has the potential to inhibit corrosion in iron. A higher concentration of melinjo seed extract correlated with a lower corrosion rate. The highest corrosion rate was 6.7x10-2 g/cm² day at 0% concentration. The lowest corrosion rate was 1.6x10-2 g/cm² day at a 15% concentration of melinjo seed extract. The optimum inhibition efficiency was achieved at the 15% concentration, which amounted to 76%. These results indicate that melinjo seed extract is an effective bioinhibitor for ferrous metal corrosion.